2017
DOI: 10.1039/c7ra01438d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rare-earth metal oxide (Eu2O3) on the electrochemical properties of a polypyrrole/CuO polymeric composite for supercapacitor applications

Abstract: A ternary composite of polypyrrole/copper oxide/europium oxide (PPY/CuO/Eu2O3), synthesized via a facile in situ chemical oxidative polymerization method, exhibits the maximum specific capacitance of 320 F g−1 at the current density of 1 A g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 58 publications
(72 reference statements)
3
34
0
Order By: Relevance
“…For metal oxide electrode, poor cyclic stability due to structural damage during the redox process is common 47 . The coulombic/faradic efficiency was measured from ratio of discharging by charging time and demonstrates the practical applicability of electrode material for supercapacitor 48 . The coulombic efficiency increased over time and reached ~92% which validates the improved redox reversibility of electrode material 48 .…”
Section: Resultsmentioning
confidence: 82%
“…For metal oxide electrode, poor cyclic stability due to structural damage during the redox process is common 47 . The coulombic/faradic efficiency was measured from ratio of discharging by charging time and demonstrates the practical applicability of electrode material for supercapacitor 48 . The coulombic efficiency increased over time and reached ~92% which validates the improved redox reversibility of electrode material 48 .…”
Section: Resultsmentioning
confidence: 82%
“…Clear fluorescence was observed when Dy 2 O 3 and Tb 4 O 7 were used as fillers for UDMA based composites [11]. Incorporation of Eu 2 O 3 into polypyrrole/CuO results in increasing of their capacitive performances [12]. In another study, it was demonstrated that adding Dy2O3 to the polyetheretherketone based composites increase their x-ray shielding properties [13].…”
Section: Introductionmentioning
confidence: 96%
“…[ 18–20 ] On the contrary, electrode materials such as transition metal oxides (TMOs)/transition metal hydroxides (TMHOs) (RuO 2 , MnO 2 , Co 3 O 4 , NiCo 2 O 4 , Ni(OH) 2 , Co(OH) 2 , etc. ), [ 21–38 ] conducting polymers (CPs) (polyaniline [PANI], polypyrrole [PPy], PTh, poly(3,4,‐ethylenedioxythiophene) [PEDOT]), [ 39–46 ] transition metal chalcogenides (TMCs) (MoS 2 , VS 2 , NiS 2 , CoSe, NiSe, MoSe 2 , MoTe 2 , NiCo 2 S 4 ), [ 47–73 ] and other materials such as MXene, [ 8,74–78 ] black phosphorus, [ 79 ] metal nitrides, rare‐earth oxide/hydroxides, [ 80–84 ] and metal–organic framework (MOF) [ 85–87 ] show a redox reaction mechanism which comes under pseudocapacitance category. Generally, these two electrode materials are merged to form composites or hybrids electrode materials are exhibiting better electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%